Implementasi CSR Perusahaan Migas Dalam Pelayanan Kesejahteraan Masyarakat di Tuban: (Studi implementasi CSR Joint Operating Body Pertamina Petrochina East Java) - Huda, Muhammad Miftahul (Asketik: Jurnal Agama dan Perubahan Sosial, 2019)
This paper is a result of a research study about the impact of Corporate Social Responsibility (CSR) of oil and gas companies on social welfare. This research specifically focuses on communities in five villages around an oil and gas Joint Operating Body managed by Pertamina and Petrochina of East Java operating in Tuban Regency, East Java Province. The company performed CSR as required by Law No.22 the Year 2001 on Oil and Gas which was further elaborated by Special Task Force for Upstream Oil and Gas Business Activities (SKK Migas) Regulation No. 017/PTK/III/2005 on Guidelines for Community Development. The research method is qualitative and descriptive. The research found that the company’s CSR implemented four programs that do not lead to good practices of community development. Many programs implemented did not align with community needs and lacked transparency – which then led to misuse of funds, and no impact on affected communities' welfare. Poverty in natural resource-rich areas is a common phenomenon known as the ‘resource course’. It is called a ‘curse’ as the natural resources were supposed to be a blessing for a prosper and prosperous community. However, the opposite often happens. This resource curse is believed can be solved by many things, in which one of which, is the company’s role through Corporate Social Responsibility (CSR). For CSR programs to work well, align with community needs, and have a sustainable impact, then the management of CSR becomes an important thing to be pushed. Transparency and accountability of CSR programs are crucial points that are required to be monitored by stakeholders. CSR is not a charity based on voluntary action, but an obligation that is the responsibility of the the company as good mining practices.